2017
DOI: 10.1021/acsnano.7b04194
|View full text |Cite
|
Sign up to set email alerts
|

On-Surface Oligomerization of Self-Terminating Molecular Chains for the Design of Spintronic Devices

Abstract: Molecular spintronics is currently attracting a lot of attention due to its great advantages over traditional electronics. A variety of self-assembled molecule-based devices are under development, but studies regarding the reliability of the growth process remain rare. Here, we present a method to control the length of molecular spintronic chains and to make their terminations chemically inert, thereby suppressing uncontrolled coupling to surface defects. The temperature evolution of chain formation was follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Interactions between unpaired electrons localized on metal centers are an important feature of the active sites of many metalloenzymes 1 , artificial catalysts 2 , and molecular magnets with possible applications such as data storage, quantum computing or magnetic materials [3][4][5][6][7][8][9][10][11] . Such interactions are usually not mediated directly by magnetic interactions due to the distance between the spin centers, but rather via a combination of Coulomb interaction and exchange interactions resulting from the Pauli exclusion principle.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between unpaired electrons localized on metal centers are an important feature of the active sites of many metalloenzymes 1 , artificial catalysts 2 , and molecular magnets with possible applications such as data storage, quantum computing or magnetic materials [3][4][5][6][7][8][9][10][11] . Such interactions are usually not mediated directly by magnetic interactions due to the distance between the spin centers, but rather via a combination of Coulomb interaction and exchange interactions resulting from the Pauli exclusion principle.…”
Section: Introductionmentioning
confidence: 99%
“…An emerging possibility to address these challenges is to develop hybrid materials in which surfaces are functionalized with organic molecules. Chemical approaches using self-assembled monolayers or molecular films to manipulate the chemical, electronic, and magnetic , properties of thin films and nanostructures have been successfully applied to tune material surfaces and interfaces. Moreover, fascinating studies over the past two decades have demonstrated that chiral molecular assemblies can act as electron spin filters, a phenomenon known as the chiral-induced spin selectivity (CISS) effect (Figure ).…”
mentioning
confidence: 99%
“…Interactions between unpaired electrons localized on metal centers are an important feature of the active sites of many metalloenzymes 1 , artificial catalysts 2 , and molecular magnets with possible applications such as data storage, quantum computing or magnetic materials [3][4][5][6][7][8][9][10][11] . Such interactions are usually not mediated directly by magnetic interactions due to the distance between the spin centers, but rather via a combination of Coulomb interaction and exchange interactions resulting from the Pauli exclusion principle.…”
Section: Introductionmentioning
confidence: 99%